Dubai Groundwater well survey and soil salinity field data collection using ModeflowMap - et. al., Lala El Hoummaidi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In Dubai, groundwater and soil are threatened by over-irrigation, over-extraction, and contamination. Furthermore, the installation of packaged desalination equipment by many farm owners to overcome the challenges of deteriorating water quality caused a significant increase in salinity levels in the soil and surface level contaminants percolating to the groundwater aquifers. Thus, well-planned and executed programs should be considered to save Dubai's aquifers. As we learn more about groundwater issues in Dubai Emirate, it becomes very clear that these issues require collective and integrated responses in order to better manage the groundwater resources in the long-term future. Therefore, surveys capturing the groundwater parameters for 47,000 groundwater wells in Dubai were successfully conducted using durable smartphones where Dubai municipality teams recorded the location, type and depth of each well, and measured the flow rate, salinity and hydro-chemical profile of groundwater at each well head. This comprehensive effort is necessary to fully understand the state of Dubai's groundwater and soil resources and support the development of effective policies to efficiently manage these resources. This article describes the methods and the results of the field survey conducted using ModeflowMap Mobile application, an innovative field inspection solution developed to monitor and conduct different types of inspections of groundwater wells. In conclusion, ModeflowMap comprised an important support tool for decision makers to ensure that wells are not being over-pumped, the groundwater in the wells is of optimum quality and there’s no long-term risk to the groundwater wells through automation of work assignments, agronomic data capturing and groundwater samples collection from each well, it also integrates with other enterprise GIS systems, and generates reports and maps for monitoring inspections real-time.